2013
DOI: 10.11607/prd.0932
|View full text |Cite
|
Sign up to set email alerts
|

Results of Vertical Bone Augmentation with Autogenous Bone Block Grafts and the Tunnel Technique: A Clinical Prospective Study of 10 Consecutively Treated Patients

Abstract: The aim of this study was to report the outcome of the management of alveolar crest vertical defects using the tunnel technique approach associated with autogenous bone blocks prior to implant placement in 10 partially dentate consecutively treated patients. Four clinical linear measurements were taken: maximal extension of the vertical defect (VD) at the time of the augmentation procedure (time 0), vertical bone graft (VBG) recorded at time 0, bone resorption at implant placement (time 1), and bone resorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…Following Khoury and Khoury's bone block management approach, 9,23,24 the bone block was bisected into two thinner cortical lamina and then grafted in combination with autogenous particles bone scraped from the same lamina (Fig 8). When needed, a sinus lift procedure was done in conjunction with the autogenous bone grafting procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Following Khoury and Khoury's bone block management approach, 9,23,24 the bone block was bisected into two thinner cortical lamina and then grafted in combination with autogenous particles bone scraped from the same lamina (Fig 8). When needed, a sinus lift procedure was done in conjunction with the autogenous bone grafting procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of up to 40% for graft exposure and resorption in the mid or long term are the main drawbacks of using onlay bone grafts to treat posterior vertical mandibular defects (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…10 Rates of up to 40% for graft exposure and resorption in the mid or long term are the main drawbacks of using onlay bone grafts to treat posterior vertical mandibular defects. 15 Khoury and other authors 11,15,16 have described the combination of a tunnel approach with 3D reconstruction using a bone block graft sectioned into two thinner layers (width of 1-2 mm) as a simple and effective treatment that offers very good short-term outcomes and stability over time. Cordaro et al 17 reported a 41.5% loss in bone height in the first 6 months when the chin or mandibular ramus was used as the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the low incidence of graft exposure in this study is in agreement with previous reports on the use of the tunnel technique for bone augmentation. 16,21,22 The two vertical vestibular incisions offer an appropriate minimally invasive access to the defect for placing and correctly fixating the cortical laminae with microscrews. Sub-periosteal tunnelling in the posterior mandible often requires dissection of mental nerve branches, especially for extensive defects that involve the premolar area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation